Analisis Penerapan Peraturan Menteri Keuangan Nomor 38/PMK.11/2013 Tentang Dasar Pengenaan Pajak Nilai Lain Pada Pajak Pertambahan Nilai Jasa Freight Forwarding Di PT. Trans Continent - Sandag, Eltie Christi; Karamoy, Herman; Lambey, Linda (Universitas Sam Ratulangi, 2017)
Abstract.This study aims to (1) analyze the conformity of the application of Regulation of the Minister of Finance No. 38/PMK.011/2013 on the Basic Taxation of Other Value on Value Added Tax of PT.Trans Continent freight forwarding services, (2) analyze the efforts made in overcoming the overpayment of VAT in connection with the application of Regulation of the Minister of Finance No. 38/PMK.011/ 2013 in accordance with the provisions of applicable tax laws. This is a qualitative research with case study approach. Data were obtained through the technique of in-depth interviews, observation and documentation study. The key informants were determined by purposive sampling in order to attain the correct and accurate information. Triangulation techniques were used to test the validity of data and data sources. The transcript data described from the interviews were analyzed using analytical methods consisting of the giving of themes/coding, conceptualizing scientific statements and interpreting them in narrative form. The results of the research indicate that the Basic of Taxation of Other Value is imposed on services which have element of freight charges conducted by PT.Trans Continent has been implemented based on Regulation of the Minister of Finance No.38/PMK.011/2013. However, the issuance of this Regulation of the Minister of Finance has not yet considered the overall freight forwarding activities as a single entity, in which the freight forwarding service company also provides services that have no element of freight charges, and in its business turnover in doing their transactions with other Taxable Entrepreneurs who do not use Basic Imposition Other Value Tax. Continuous compensation efforts are made to overcome the overpayment of Value Added Tax (VAT) in connection with the application of Regulation of the Minister of Finance No.38/PMK.011/2013 on the Tax Basis of Other Valuation in its settlement, which is also not followed by knowledge on other provisions governing taxation (regulations determined by Directorate General of Taxation No.PER-11/ PJ/2013).Keywords: Analysis, Value Added Tax (VAT), Tax Basis of Other Valuation, Freight ForwardingAbstrak. Penelitian ini bertujuan untuk (1) menganalisis kesesuaian penerapan Peraturan Menteri Keuangan Nomor 38/PMK.011/2013 tentang Dasar Pengenaan Pajak (DPP) nilai lain pada Pajak Pertambahan Nilai (PPN) jasa freight forwarding di PT.Trans Continent, (2) menganalisis upaya yang dilakukan dalam mengatasi kelebihan bayar PPN sehubungan dengan penerapan Peraturan Menteri Keuangan Nomor 38/PMK.011/2013 sesuai dengan ketentuan peraturan perpajakan yang berlaku. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data diperoleh melalui teknik wawancara yang mendalam, studi dokumentasi dan observasi. Informan kunci ditetapkan secara purposive sampling dengan syarat memenuhi kriteria yang ditetapkan untuk mendapatkan informasi yang tepat dan akurat. Teknik triangulasi digunakan untuk menguji validitas data dan sumber data. Data transkrip yang diuraikan dari hasil wawancara dianalisis menggunakan metode analisis yang terdiri dari pemberian tema/coding, konseptualisasi pernyataan ilmiah dan menginterpretasikannya dalam bentuk narasi. Hasil penelitian menunjukkan bahwa Dasar Pengenaan Pajak (DPP) nilai lain dikenakan atas jasa yang memilki unsur freight charges yang dilakukan oleh PT. Trans Continent dilaksanakan berdasarkan Peraturan Menteri Keuangan (PMK) No 38/PMK.011/2013, namun terbitnya PMK ini belum melihat kegiatan freight forwarding secara keseluruhan yang merupakan satu kesatuan usaha, yang dimana perusahaan jasa freight forwarding juga menyediakan jasa yang tidak memiliki unsur freight charges, dan dalam perputaran usahanya bertransaksi dengan Pengusaha Kena Pajak (PKP) lain yang tidak menggunakan Dasar Pengenaan Pajak (DPP) nilai lain . Upaya kompensasi yang terus menerus dilakukan dalam mengatasi kelebihan bayar PPN sehubungan dengan penerapan PMK No 38/PMK.011/2013, dalam penyelesainnya juga tidak diikuti dengan pengetahuan akan ketentuan-ketentuan lain yang mengatur tentang perpajakan (yakni peraturan Direktorat Jendral Pajak Nomor PER-11/PJ/2013). Kata Kunci: Analisis, Pajak Pertambahan Nilai, Dasar Pengenaan Pajak Nilai Lain, Freight Forwarding